2018
DOI: 10.4236/ijg.2018.91005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Groundwater Flow and Saltwater Intrusion in the Coastal Aquifer of Fum Al Wad, Province of Laayoun, Morocco

Abstract: Saltwater intrusion caused by groundwater over-exploitation from coastal aquifers poses a severe problem in many regions. The Fum Al Wad aquifer is located between Atlantic Ocean in the West and Laayoun in the East. This aquifer covers an area of 250 Km 2 , and represents an essential water resource for Laayoun city and the periphery regions. It is heavily exploited for water supply, agriculture and industry. The freshwater-saltwater interface is affected by groundwater extraction by public supplies, irrigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Due to continuous population growth and impaired water supply, future generations will have many challenges including the accessibility of clean and freshwater (Weinrich et al, 2012). Mokhtar et al (2018) studied the groundwater flow and SWI in Fum Al Wad coastal aquifer located in Laayoune (27.15° N, 13.19° W) and reported that the farmers using groundwater for irrigation and other purposes must be thoroughly informed of the serious issues associated with overexploitation and over pumping of groundwater. Maity et al (2018) reported that lack of awareness amongst farmers, unwilling involvement of the governing bodies and unavailability of other water sources in Purba Midnapur district (21.94° N, 87.78° E), poses major hurdles in implementing aquifer improvement plans.…”
Section: Awareness Programmentioning
confidence: 99%
“…Due to continuous population growth and impaired water supply, future generations will have many challenges including the accessibility of clean and freshwater (Weinrich et al, 2012). Mokhtar et al (2018) studied the groundwater flow and SWI in Fum Al Wad coastal aquifer located in Laayoune (27.15° N, 13.19° W) and reported that the farmers using groundwater for irrigation and other purposes must be thoroughly informed of the serious issues associated with overexploitation and over pumping of groundwater. Maity et al (2018) reported that lack of awareness amongst farmers, unwilling involvement of the governing bodies and unavailability of other water sources in Purba Midnapur district (21.94° N, 87.78° E), poses major hurdles in implementing aquifer improvement plans.…”
Section: Awareness Programmentioning
confidence: 99%
“…The average thickness of the aquifer is of the order of 5 m with a water level located around 40 m deep. The water released from the aquifer is brackish with salinity close to 7 g/l [23].…”
Section: C) Hydrogeologymentioning
confidence: 99%
“…Nowadays, numerical modeling technology is an important tool for GW analysis. CC impacts, computational GW flow, and transport modeling have been investigated in many regions around the world [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%